Luteolin protects DYT-PRKRA cells from apoptosis by suppressing PKR activation - Frederick, Kenneth; Patel, Rekha C. (Frontiers in Pharmacology, 2023)
DYT-PRKRA is a movement disorder caused by mutations in the PRKRA gene, which encodes for PACT, the protein activator of interferon-induced, double-stranded RNA (dsRNA)-activated protein kinase PKR. PACT brings about PKR’s catalytic activation by a direct binding in response to stress signals and activated PKR phosphorylates the translation initiation factor eIF2 alpha Phosphorylation of eIF2 alpha is the central regulatory event that is part of the integrated stress response (ISR), an evolutionarily conserved intracellular signaling network essential for adapting to environmental stresses to maintain healthy cells. A dysregulation of either the level or the duration of eIF2 alpha phosphorylation in response to stress signals causes the normally pro-survival ISR to become pro-apoptotic. Our research has established that the PRKRA mutations reported to cause DYT-PRKRA lead to enhanced PACT-PKR interactions causing a dysregulation of ISR and an increased sensitivity to apoptosis. We have previously identified luteolin, a plant flavonoid, as an inhibitor of the PACT-PKR interaction using high-throughput screening of chemical libraries. Our results presented in this study indicate that luteolin is markedly effective in disrupting the pathological PACT-PKR interactions to protect DYT-PRKRA cells against apoptosis, thus suggesting a therapeutic option for using luteolin to treat DYT-PRKRA and possibly other diseases resulting from enhanced PACT-PKR interactions.